The emergence of International business 1200-1800. Volume V : The Royal African Company - Davies, K. G. (Kenneth Gordon) (London ; New York : Routledge/Thoemmes Press, 1999)
Introduction. Capital and finance. Monopoly and competition. The company in England. Shipping. The company in Africa. The company in the West Indies.
Keywords: African; Slave-trade.; Royal African Company; Slave-trade -- Africa